Humanism in Devkota’s Bhikhari - Adhikari, Kumar (Literary Studies, 2016)
This paper analyzes some of the poems from Laxmi Pd. Devkota’s Bhikhari, one of the popular compilations of Nepali poetry. Devkota is primarily a humanist poet. He is also the leading Nepali poet who popularized Romantic poetry in Nepali literature. In Bhikhari, Devkota seems more like a ‘romantic humanist’. The paper tries to trace the root of ‘humanism’ in general, and how English Romantic poets accommodated it in their Romantic philosophy later in the 19th century. In short, humanism believes that individuals have everything they need to grow and develop to their fullest potential. This article is a reading of Devkota’s some of the poems from his collection Bhikhari from the perspective of humanism.